2009
DOI: 10.1109/tcsi.2008.2008286
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Waveform Relaxation Methods for Longitudinal Partitioning of Transmission Lines

Abstract: Abstract-Waveform relaxation (WR) is a technique whichcan be used to solve large systems of ordinary differential equations (ODEs). It is especially suitable for the parallel solution of ODEs with multiple time scales, and has been successfully used for solution of electronic circuits and for solving partial differential equations (PDEs). The main issue limiting the utility of waveform relaxation is the class of problems with strong subsystem to subsystem couplings and long analysis time intervals resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…For more information, see [30,7]. Waveform relaxation methods should thus never be used with classical transmission conditions, also when applied to circuits; optimized transmission conditions have also been proposed and analyzed for circuits, see for example [1,2] and references therein. …”
Section: Gander Halpern and Nataf 1999mentioning
confidence: 99%
“…For more information, see [30,7]. Waveform relaxation methods should thus never be used with classical transmission conditions, also when applied to circuits; optimized transmission conditions have also been proposed and analyzed for circuits, see for example [1,2] and references therein. …”
Section: Gander Halpern and Nataf 1999mentioning
confidence: 99%
“…Domain decomposition methods are particularly well-adapted for the parallel solution of linear systems that appear in finite difference and finite element methods. Among the various domain decomposition methods [24,28], we focus our attention here on the Classical Schwarz Waveform Relaxation (CSWR) DDM [1,13,25,26,27,28,29,30,31,32,36]. Even if this method has received much attention over the past years for many applications, to the best of the authors' knowledge, the first application to the Schrödinger equation can be found in [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, for tightly coupled MTLs, the above algorithm may require a large number of iterations to converge. An alternative waveform relaxation algorithm based on longitudinal partitioning of the line into lumped RLGC subcircuits has also been proposed in [5]. Generally, longitudinal partitioning of the transmission line using the conventional lumped RLGC model results in strong coupling between the subcircuits, leading to slow and inefficient convergence properties of the algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, longitudinal partitioning of the transmission line using the conventional lumped RLGC model results in strong coupling between the subcircuits, leading to slow and inefficient convergence properties of the algorithm. To mitigate the above problem, in [5] the convergence was accelerated by exchanging additional voltage/current waveforms between the subcircuits followed by optimization routines. However, longitudinal partitioning of the line using lumped RLGC subcircuits is still not suitable for modeling long delay lines as the number of subcircuits required to implicitly model the delay of the line can quickly become exorbitant [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation